Konstruk Minat Beli Sepeda Motor Honda di Bekasi: Dampak Kualitas Produk dan Taktik Promosi - Manurung, Johan Andrew; Dini, Julia Rachma; Zebua, Elvin Agustini; Abdullah, Muhammad (Jurnal Manajemen Dirgantara, 2024)
This study investigates the effects of product quality and promotional strategies on consumer purchase interest in Honda motorcycles within Bekasi Regency, a region notable for its substantial market potential. As a crucial component of Indonesia's economic framework, the automotive sector-particularly motorcycles-plays a significant role. Honda, a leading brand in this competitive market, strives to sustain its market dominance through continual product innovation and dynamic promotional activities. Despite this, the interplay between product quality and promotional efforts in specific local contexts, such as Bekasi Regency, remains insufficiently explored. Employing a quantitative causal research design, this study surveyed Honda motorcycle consumers in Bekasi Regency using purposive sampling methods. Data analysis was performed with SPSS version 25. Findings reveal that both product quality and promotional tactics have a substantial impact on consumer purchase interest, both independently and in combination. Effective promotional activities and high-quality products significantly enhance Honda's market appeal in this locale. The insights gained from this research offer valuable implications for automotive marketing strategies, highlighting the importance of targeted promotions and exceptional product quality in influencing consumer behavior. These results are not only pertinent to Bekasi Regency but also provide a basis for extending research to other regions with similar market dynamics. Future studies should consider additional influencing factors and broaden the geographic scope to achieve a more comprehensive understanding.